Transition of Electric Mobility in Colombia: Technical and Economic Evaluation of Scenarios for the Integration of E-taxis in Bucaramanga - Muñoz Maldonado, Yecid Alfonso; Acevedo, César; Jerez, Edward; Sarmiento, Carlos; De La Rosa, Miguel; Ospino, Adalberto (International Journal of Energy Economics and Policy, 2021)
Globally, the transport sector has been directed towards electric mobility by policies, regulations, development strategies and economic incentives. The transport sector has an important strategic role in the economic development of a country, the sustainability of this sector has an impact on political and scientific discussions due to its environmental impact. In Colombia, the global targets for reducing polluting emissions begin to drive the renewal of the automotive park towards electric mobility, therefore, this research was carried out with the aim of carrying out a technical and economic analysis of scenarios for the e-taxis in Bucaramanga, the incentives applied in the two projects developed in the two most important cities of Colombia were taken as the basis to compare possible implementation scenarios in the short and medium term. Three technologies (gasoline, gas and electric) were evaluated that were tested using the TAC/km indicator, the financial viability was assessed based on two financial kindness criteria (NPV and IRR). The results obtained allow to conclude two strategies that make it possible to incorporate the e-taxis in Bucaramanga, 1) exemption from payment of taxi registration, in case of incorporation of a new vehicle; 2) economic incentive of more than 20% at the time of purchase of the EV, accompanied by a 25% increase in the cost of the minimum service fee, in the case of the replacement of a taxi. Keywords: electric taxi Colombia, e-taxi policies, electric mobility, electric vehicle, public transport sector. JEL Classifications: Q01, Q4, Q42 DOI: https://doi.org/10.32479/ijeep.11084